2010
DOI: 10.1590/s1809-29502010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Influência do tempo de hospitalização sobre o desenvolvimento neuromotor de recém-nascidos pré-termo

Abstract: O objetivo deste estudo foi avaliar a influência do tempo de hospitalização sobre o desenvolvimento neuromotor de recém-nascidos pré-termo (RNPT). Foi feito um estudo prospectivo com 67 RNPT de idade gestacional <36 semanas. O desenvolvimento neuromotor foi avaliado pela escala motora infantil de Alberta (Alberta infant motor scale, AIMS), aplicada no ambulatório de seguimento, quando os RN tinham mediana de idade corrigida de 39 a 44 semanas. Para a análise comparativa, os RNPT foram distribuídos em dois g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
23

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 17 publications
0
12
0
23
Order By: Relevance
“…Research that addresses conditions of birth and the influence of multiple risk factors reveals incidences and neurodevelopmental sequelae that interfere significantly in the quality of life and social inclusion (4)(5)13) . A recent study reported that the results about infant development translate to the rate of development of the country, as well as those of education, health conditions and level of attention to health (5) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research that addresses conditions of birth and the influence of multiple risk factors reveals incidences and neurodevelopmental sequelae that interfere significantly in the quality of life and social inclusion (4)(5)13) . A recent study reported that the results about infant development translate to the rate of development of the country, as well as those of education, health conditions and level of attention to health (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Three, however, were unaware of any type of developmental delay of the child. Studies about the monitoring of infant development, in follow-up programs (4,6,17) , refer that the families can count on support for orientation, constituting a factor of protection to the infant development. Furthermore, the implementation of follow-up is recommended, however the network of assistance provided to the infant discharged from the NICU is deficient in the country (17) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations